Graphene as a Novel Matrix for the Analysis of Small Molecules by MALDI-TOF MS - Dong, Xiaoli; Cheng, Jinsheng; Li, Jinghong; Wang, Yinsheng (Analytical chemistry (Washington), 2010)
Graphene was utilized for the first time as a matrix for the analysis of low molecular weight compounds using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Polar compounds including amino acids, polyamines, anticancer drugs, and nucleosides could be successfully analyzed. Additionally, nonpolar compounds including steroids could be detected with high resolution and sensitivity. Compared with a conventional matrix, graphene exhibited a high desorption/ionization efficiency for nonpolar compounds. The graphene matrix functions as a substrate to trap analytes, and it transfers energy to the analytes upon laser irradiation, which allows for the analytes to be readily desorbed/ionized and interference of intrinsic matrix ions to be eliminated. The use of graphene as a matrix avoided the fragmentation of analytes and provided good reproducibility and a high salt tolerance, underscoring the potential application of graphene as a matrix for MALDI MS analysis of practical samples in complex sample matrixes. We also demonstrated that the use of graphene as an adsorbent for the solid-phase extraction of squalene could improve greatly the detection limit. This work not only opens a new field for applications of graphene, but also offers a new technique for high-speed analysis of low molecular weight compounds in areas such as metabolism research and natural product characterization.